Behavioral protocol for early assessment and intervention for infants at risk of autism (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The Autism Spectrum Disorders (ASD) diagnosis is commonly given at the age three or older, which precludes early interventions. There are few Brazilian studies that focused on ASD early detection on high-risk infants. The aim of this paper is to present an early assessment behavioral protocol to assess ASD risk factors on siblings of 7 to 36 months old. The assessment was developed as a tool to assess the infant’s performance at the natural environment. The protocol is structured with activities that the child performs with the caregiver, creating opportunities to evoke target behaviors identified in the literature on high-risk factors. Preliminary findings of the evaluation of atypical development factors demonstrated correlation with the assessment results of specialists.
Keywords: behavior analysis, high-risk population, early assessment